A tunable and sizable bandgap of a g-C3N4/graphene/g-C3N4 sandwich heterostructure: a van der Waals density functional study. Issue 15 (3rd April 2017) - Dong, M. M.; He, C.; Zhang, W. X.
Abstract : Uniaxial strain can effectively tune the electronic properties of a g-C3 N4 /SLG/g-C3 N4 sandwich heterostructure. Abstract : The structural and electronic properties of a g-C3 N4 /graphene/g-C3 N4 (g-C3 N4 /SLG/g-C3 N4 ) sandwich heterostructure have been systematically investigated using density functional theory with van der Waals corrections. The results indicate that the band gap of the g-C3 N4 /SLG/g-C3 N4 sandwich heterostructure can be opened to 106 meV without strain. Applying strain is a promising way to tune the electronic properties of a sandwich heterostructure. After applying uniaxial strain, the heterostructure can withstand larger tensile strain than compression strain without damaging the structure and the band gap is more easily increased by the X -direction strain. When the 5% X -direction strain is applied, the band gap could be opened to 525 meV and meanwhile maintain a high carrier mobility. These electronic properties may provide a potential application in nanodevices.